2010
DOI: 10.1073/pnas.1017069108
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical model for a propofol-induced α-rhythm associated with loss of consciousness

Abstract: Recent data reveal that the general anesthetic propofol gives rise to a frontal α-rhythm at dose levels sufficient to induce loss of consciousness. In this work, a computational model is developed that suggests the network mechanisms responsible for such a rhythm. It is shown that propofol can alter the dynamics in thalamocortical loops, leading to persistent and synchronous α-activity. The synchrony that forms in the cortex by virtue of the involvement of the thalamus may impede responsiveness to external sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
405
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 348 publications
(457 citation statements)
references
References 36 publications
31
405
3
4
Order By: Relevance
“…A similar feature has been observed during burst suppression induced by isoflurane general anesthesia, in which slow-wave and delta activity persists during the burst epochs (11). The propofol-induced alpha is thought to involve potentiation of gamma aminobutyric acid (GABA) inhibitory currents in thalamocortical loops (20,21). The recovery of these mechanisms during bursts suggests that a more global dynamic perturbation, (i.e., not simply an increase in GABA, must be responsible for creating the epochs of suppression).…”
Section: Additional Data and Constraintsmentioning
confidence: 56%
See 2 more Smart Citations
“…A similar feature has been observed during burst suppression induced by isoflurane general anesthesia, in which slow-wave and delta activity persists during the burst epochs (11). The propofol-induced alpha is thought to involve potentiation of gamma aminobutyric acid (GABA) inhibitory currents in thalamocortical loops (20,21). The recovery of these mechanisms during bursts suggests that a more global dynamic perturbation, (i.e., not simply an increase in GABA, must be responsible for creating the epochs of suppression).…”
Section: Additional Data and Constraintsmentioning
confidence: 56%
“…We demonstrate the main result using a purely cortical network consisting of reciprocally coupled interneurons and pyramidal cells. As shown previously (20,37), such a network can be used to explain the progressive reduction in frequency of EEG oscillations observed during induction of general anesthesia via propofol. The mechanism in those models was a drug-induced potentiation of GABA A inhibitory postsynaptic potentials.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Different cortical layers in prelimbic cortex display different connectivity patterns with thalamus and other cortical and subcortical areas. Also, the model put forward by Ching et al (14) assumed a generic prefrontal layer 5 neuron. Therefore, we investigated the possibility of different layers being differentially affected by propofol.…”
Section: Layers Of Prefrontal Cortex Are Differentially Affected By Pmentioning
confidence: 99%
“…Electroencephalogram (EEG) recordings in humans during gradual induction of unconsciousness with propofol show the appearance of frontal β oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at the onset of sedation, followed by the appearance of coherent frontal α (8-12 Hz) oscillations (7)(8)(9)(10) and widespread slow (0.1-1 Hz) and δ (1-4 Hz) oscillations (7,11,12) when subjects no longer respond to sensory stimuli. Biophysical models of neuronal dynamics have shown that whereas α and β oscillations can be generated by propofol's actions in cortex alone (13), coherent α oscillations require the participation of both thalamus and cortex (14). Imaging studies in humans have shown that propofol disrupts functional relationships between cortex and thalamus, eliciting a greater degree of disruption between cortex and higher-order thalamic nuclei compared with first-order nuclei (15).…”
mentioning
confidence: 99%